Application and limitation of nanomedicine in different cardiovascular disease - NAMITA SHARMA, (International Journal of Pharma and Bio Sciences, 2018)
The merged fields of Nanotechnology and Medicine, Nano medicine utilizes the knowledge of nanoparticles to deal with human health problems. Diagnosis, detection and imaging are the crucial stages for prevention of diseases. This review enlightens the strategies applied to improve the diagnosis and therapy for cardiovascular disorders like hypertension, atherosclerosis, myocardial infarction and thrombosis and new methods developed to deliver drug through proper delivery system at specific site composed of nanoparticles/polymers and drug. This advances and enhances the present status of the treatment in medicine for curing these disorders but low permeability, non-biodegradability and toxicity of some polymers limit the use of nanoparticles.